Diversity of Waterbirds in the Sebuku Strait Kotabaru, South Kalimantan - Maulana Khalid Riefani; Mochamad Arief Soendjoto (Universitas Sebelas Maret, 2015)
This research is to determine the diversity of waterbirds in the Sebuku Strait (Pulau Laut Timur and Pulau Sebuku), Kotabaru, South Kalimantan. Communities of waterbirds identified in the mangrove forest (HM); rice paddies and ponds (Sw-Ta); wetlands and ponds (Ra-Te); open land, savannas, and shrublands (LT-PR-SB), beach front and strait (TPT-Se). The Research used point methods or point of abundance and exploration in the habitat types, at 6:00 - 11:00 pm (morning) and 1:00 - 6:00 pm (afternoon) in March until May 2014. Analysis the type of habitat, name of the species, and number of waterbirds were identified. Around the Sebuku Strait were found 28 species of 9 families waterbirds. Diversity of waterbirds around Sebuku Strait was high (H '= 3.237). It was found various families of waterbirds, i.e. family of Ardeidae (11 species), Alcedinidae (4 species), Anatidae (2 species), Anhingidae, Ciconiidae, Fregatidae, Rallidae, Recurvirostridae, and Scolopacidae (1 species). Sixteen species protected by government regulations No. 7 of 1999, only one species in Appendix I CITES (Convention on International Trade in Endangered Species).Keywords: Sebuku straight, diversty, waterbirds, protected, CITES